From acute tubular injury to tubular repair and chronic kidney diseases – KIM-1 as a promising biomarker for predicting renal tubular pathology - Ping L. Zhang; Ming-Lin Liu (Current Research in Physiology, 2025)
Kidney Injury Molecule-1 (KIM-1) has emerged as a significant biomarker and mechanistic player in kidney pathology, particularly in acute kidney injury (AKI). Normally absent in healthy kidney proximal tubules, KIM-1 becomes upregulated specifically along the proximal tubule cells' surface in response to acute injury, reflecting the differential vulnerability of convoluted versus straight proximal tubules. Functionally, KIM-1 aids proximal tubules in clearing apoptotic cells and moderating inflammatory responses, thereby helping to prevent excessive immune activation during the early stages of injury. Clinically, KIM-1 is a sensitive, non-invasive biomarker for detecting proximal tubular injury, allowing for assessment in urine, plasma samples, and tissue biopsies in AKI. However, if tubular injury persists without repair, prolonged KIM-1 expression can drive chronic inflammatory responses and interstitial fibrosis, leading to chronic kidney disease (CKD). In addition, KIM-1's role may extend further into promoting tubular dedifferentiation, potentially contributing to renal cell carcinoma under certain conditions. Over the past two decades, KIM-1 research has reshaped our understanding of kidney pathophysiology and immunology, spanning acute injury responses to chronic disease progression. This review aims to provide an updated synthesis of recent findings, highlighting KIM-1's role across the spectrum of renal injury and repair.